Dietary galacto-oligosaccharides prevent airway eosinophilia and hyperresponsiveness in a murine house dust mite-induced asthma model. Issue 1 (December 2015) - Verheijden, Kim; Willemsen, Linette; Braber, Saskia; Leusink-Muis, Thea; Delsing, Dianne; Garssen, Johan; Kraneveld, Aletta; Folkerts, Gert
Abstract Background Allergic asthma is strongly associated with the exposure to house dust mite (HDM) and is characterized by eosinophilic pulmonary inflammation and airway hyperresponsiveness (AHR). Recently, there is an increased interest in using dietary oligosaccharides, also known as prebiotics, as a novel strategy to prevent the development of, or reduce, symptoms of allergy. Aim We investigated the preventive capacity of dietary galacto-oligosaccharides (GOS) compared to an intra-airway therapeutic treatment with budesonide on the development of HDM-induced allergic asthma in mice. Methods BALB/c mice were intranasally sensitized with 1 μg HDM on day 0 followed by daily intranasal challenge with PBS or 10 μg HDM on days 7 to 11. Two weeks prior to the first sensitization and throughout the experiment mice were fed a control diet or a diet containing 1% GOS. Reference mice were oropharyngeally instilled with budesonide (500 μg/kg) on days 7, 9, 11, and 13, while being fed the control diet. On day 14, AHR was measured by nebulizing increasing doses of methacholine into the airways. At the end of the experiment, bronchoalveolar lavage fluid (BALF) and lungs were collected. Results Sensitization and challenge with HDM resulted in AHR. In contrast to budesonide, dietary intervention with 1% GOS prevented the development of AHR. HDM sensitization and challenge resulted in a significant increase in BALF leukocytes numbers, which was suppressed by budesonide treatment and dietary intervention with 1% GOS. Moreover, HDM sensitization and challenge resulted in significantly enhanced concentrations of IL-6, CCL17, IL-33, CCL5 and IL-13 in lung tissue. Both dietary intervention with 1% GOS or budesonide treatment significantly decreased the HDM-induced increased concentrations of CCL5 and IL-13 in lung tissue, while budesonide also reduced the HDM-enhanced concentrations of IL-6 and CCL17 in lung tissue. Conclusion Not only did dietary intervention with 1% GOS during sensitization and challenge prevent the induction of airway eosinophilia and Th2-related cytokine and chemokine concentrations in the lung equally effective as budesonide treatment, it also prevented AHR development in HDM-allergic mice. GOS might be useful for the prevention and/or treatment of symptoms in asthmatic disease.